Factors affecting laser power in retinal Navilas laser treatment - Höh, Alexandra E.; Marx, Stefanie; Dithmar, Stefan (Graefe's archive for clinical and experimental ophthalmology, 2015)
PurposeTo evaluate the effect of patient-associated factors on the minimum laser power needed for a mild visible burn in focal laser treatments using the 532 nm Navilas laser system.MethodsWe conducted a monocentric prospective pilot study of 58 eyes of 40 patients with diabetic macular edema. The following parameters were analysed: axial length, refraction, iris pigmentation, lens status, lens grading and densitometry, retinal and choroidal thickness and focus setting during treatment. Laser power was adjusted to produce mild, barely visible burns. Retinal laser burn size was measured 30 min after treatment.ResultsFocus setting is significantly correlated with retinal lesion size (r = 0.50, p = 0.001) and laser power (r = 0.44, p < 0.001). Axial length only correlated with laser power when the effect of focus was controlled. Phakic eyes needed more laser power than pseudophakic eyes (78.3 versus 67.2 mW, p = 0.051). No correlation of laser power with any other factor could be found.ConclusionsAmong the examined parameters, focus setting had the strongest effect on the laser power needed to produce a mild visible burn. The association of focus with laser power can be explained by the focus-dependent change of retinal spot size. Lens status (phakic versus pseudophakic patients) seems to influence laser light transmission in the examined age group.
Published online: 27 August 2014
Gesehen am 11.04.2017